OKSİDATİF DNA HASARI VE YAŞLANMA - BURÇAK, Gülden; ANDİCAN, Gülnur (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Reactive oxygen species (ROS) are formed in all living organisms as a by-product of normal metabolism and as a consequence of exposure to environmental agents. ROS attack on DNA generates a multiplicity of DNA damage products, including modified bases. One of the most common oxidative DNA lesions is 8-hydroxy deoxyguanosine (8OHdG). 8OHdG is regarded as a biomarker of oxidative DNA damage. This lesion induces G/C to T/A transversion mutation during replication of DNA. Results.- Mitochondria are both a major source of oxidants and a target for their damaging effects. Accumulation of oxidative mtDNA lesions plays a major role in mitochondrial dysfunction in aging. Specifically, the ageassociated mitochondrial DNA deletions focally accumulate in postmitotic brain and skeletal muscle. The rate of mitochondrial ROS generation in post-mitotic tissues is negatively correlated with longevity in animals. Decrease in bioenergy, organ dysfunction and apoptosis are consequences of mitochondrial dysfunction .Apoptosis occurring under conditions of augmented and persistent oxidative stress is known to be increased in age associated Alzheimer’s disease or Parkinson. Conclusion.- Caloric restriction which decreases mitochondrial ROS generation and oxidative damage to mitochondrial DNA is the only experimental manipulation capable of decreasing the rate of aging.